Effects of surface waviness on heat and fluid flow in a nanofluid filled closed space with partial heating - Abu-Nada, Eiyad; Öztop, Hakan Fehmi; Pop, Ioan (Springer, 2016)
The current computational study focused on the effects of surface waviness on heat and fluid flow in a partially heated cavity filled with a nanofluid. The cavity has a partial heater and a wavy wall which is kept cooled isothermally. The current study investigated the effects of the heat and fluid flow in the cavity due to the cooled wall waviness. The study covered a wide range of Rayleigh numbers (10(3)-10(5)), nanofluid volume fraction (0-9 %), surface waviness ratio, non-dimensional length of the heater (0.25-0.75) and non-dimensional location of the heater (0.25-0.75). It is found that the location and the length of the heater are significant parameters on heat and fluid flow. However, the cooled wall surface waviness does not influence the heat transfer substantially.
Keywords: Water-Cuo Nanofluid; Natural-Convection; Entropy Generation; Mixed Convection; Cavity; Temperature; Enclosures; Size